2023
DOI: 10.5194/hess-2023-108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulating sub-hourly rainfall data for current and future periods using two statistical disaggregation models – case studies from Germany and South Korea

Abstract: Abstract. Simulation of fast reacting hydrological systems often requires sub-hourly precipitation data to develop appropriate climate adaptation strategies and tools, i.e. upgrading drainage systems and reducing flood risks. However, this sub-hourly data is typically not provided by measurements and atmospheric models, and many statistical disaggregation tools are applicable only up to an hourly resolution. Here two different models for disaggregation of precipitation data from daily to sub-hourly scale are p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…As the disaggregated sub-daily rainfall covered the same time period as the record sub-daily rainfall, it was possible to directly compare the maximum rainfall from criti storm durations for the size of the catchment, namely those from 30 min to 360 min, each year. While the MoF is not intended to replicate recorded sub-daily rainfall nor used for hindcasting [38][39][40] and in turn unlikely to replicate recorded rainfall, compari the disaggregated rainfall to the nearby Toowoomba Airport gauge for these critical sto durations (refer to Figure 5) showed that it was able to maintain key statistics, includi As the disaggregated sub-daily rainfall covered the same time period as the recorded sub-daily rainfall, it was possible to directly compare the maximum rainfall from critical storm durations for the size of the catchment, namely those from 30 min to 360 min, for each year. While the MoF is not intended to replicate recorded sub-daily rainfall nor be used for hindcasting [38][39][40] and in turn unlikely to replicate recorded rainfall, comparing the disaggregated rainfall to the nearby Toowoomba Airport gauge for these critical storm durations (refer to Figure 5) showed that it was able to maintain key statistics, including the median and mean.…”
Section: Determination Of the Number Of Storm Classesmentioning
confidence: 99%
“…As the disaggregated sub-daily rainfall covered the same time period as the record sub-daily rainfall, it was possible to directly compare the maximum rainfall from criti storm durations for the size of the catchment, namely those from 30 min to 360 min, each year. While the MoF is not intended to replicate recorded sub-daily rainfall nor used for hindcasting [38][39][40] and in turn unlikely to replicate recorded rainfall, compari the disaggregated rainfall to the nearby Toowoomba Airport gauge for these critical sto durations (refer to Figure 5) showed that it was able to maintain key statistics, includi As the disaggregated sub-daily rainfall covered the same time period as the recorded sub-daily rainfall, it was possible to directly compare the maximum rainfall from critical storm durations for the size of the catchment, namely those from 30 min to 360 min, for each year. While the MoF is not intended to replicate recorded sub-daily rainfall nor be used for hindcasting [38][39][40] and in turn unlikely to replicate recorded rainfall, comparing the disaggregated rainfall to the nearby Toowoomba Airport gauge for these critical storm durations (refer to Figure 5) showed that it was able to maintain key statistics, including the median and mean.…”
Section: Determination Of the Number Of Storm Classesmentioning
confidence: 99%
“…As the disaggregated sub-daily rainfall covered the same time period as the recorded sub-daily rainfall, it was possible to directly compare the maximum rainfall from critical storm durations for the size of the catchment, namely those from 30 min to 360 min, for each year. While the MoF is not intended to replicate recorded sub-daily rainfall nor be used for hindcasting [38][39][40] and in turn unlikely to replicate recorded rainfall, comparing the disaggregated rainfall to the nearby Toowoomba Airport gauge for these critical storm durations (refer to Figure 5) showed that it was able to maintain key statistics, including the median and mean. This result provided additional support for the use of the MoF and the adoption of class option 2.…”
Section: Determination Of the Number Of Storm Classesmentioning
confidence: 99%